Synopsis: Unlocking agricultural efficiency: A stochastic frontier analysis of smallholder farmers in Rwanda - Benimana, Gilberthe Uwera; Warner, James; Missiame, Arnold Kwesi (International Food Policy Research Institute, 2025)
This study assesses the technical efficiency of smallholder farmers in Rwanda, with a focus on maximizing crop output value and identifying the socioeconomic drivers that shape technical efficiency.